Quality-based selection of the optimal hot air gradient drying method for anchovy and modeling of drying kinetics - Yiting Ye; Ting Zhou; Teyuan Liu; Wenzheng Shi (Aquaculture and Fisheries, 2025)
The aim of this study was to investigate the effects of hot air gradient drying on anchovy drying quality and efficiency. Anchovies were initially dried at 40 °C to until their moisture content was 40%, 45%, 50%, 55%, 60%, and 65% respectively, followed by a second drying stage at an increased temperature of 60 °C until the moisture content reached 40%. Six drying models were selected to fit the anchovy drying curves, and the Page model was found to be conformed the anchovy drying model. The drying time decreased by a minimum of 8.3% and a maximum of 33.3% as the moisture content at the turning point rose. In addition, the rehydration rate of dried anchovies increased and then decreased with increasing moisture content, while the TBA and TVBN values decreased and then increased, and there were differences in the textural properties of drying at different moisture contents. Among them, the dried anchovies with a moisture content of 55% at the turning point had the highest rehydration ratio, the lowest TBA and TVBN values, and better textural characteristics.